ANALISIS PENGARUH MEDIA INTERAKTIF DAN PERMAINAN EDUKATIF TERHADAP KONSENTRASI BELAJAR SISWA SEKOLAH DASAR: STUDI LITERATUR - Desta Marsya Fitri; Desti Marsya Fitri (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dharmas Indonesia, 2026)
: Learning concentration is a crucial factor influencing the academic success of elementary school students. However, many students still struggle to maintain focus during the learning process. One approach to addressing this issue is the use of interactive media and educational games. This study aims to analyze the impact of interactive media and educational games on the learning concentration of elementary school students through a literature review. The study employs a literature review method utilizing content analysis. Data were gathered from various scientific articles, journals, and relevant sources concerning interactive media, educational games, and elementary school students' learning concentration. An analysis of five previous studies indicates that interactive media—such as Educaplay and interactive multimedia—can enhance student engagement, interest, and attention during lessons. Furthermore, educational games—such as word guessing, charades, and ice-breaking activities—have been shown to improve students' focus and concentration. Integrating interactive media and educational games yields optimal results by capturing students' attention while simultaneously sustaining their focus throughout the learning process. Thus, interactive media and educational games serve as effective alternative teaching strategies for enhancing the learning concentration of elementary school students.